GREEN LEGISLATION, GREEN FINANCIAL CRIME, AND INDONESIA CONSTITUTIONAL LAW: A PERSPECTIVE FROM ENVIRONMENTAL JUSTICE’S THEORY - Thoriquttyas, Titis; Rohmawati, Nita (Faculty of Law Atma Jaya Yogyakarta University, 2025)
Green financial crimes are a serious threat to Indonesia's sustainable development initiatives. This research examines the ways in which financial operations affecting environmental sustainability might be regulated by constitutional legislation, preventing digital innovation from undermining environmental conservation initiatives. In order to better understand how these components, interact and how legal frameworks must change to meet these problems, this study examined the convergence of digital financial systems, green financial crimes, and Indonesian constitutional law, with a particular emphasis on precedent-setting cases. This research explores how the theory of environmental justice shapes the legal discourse on digitalization and green financial crime, and examines how Indonesian green legislation addresses the challenges posed by such crimes. This research uses qualitative techniques to analyze Indonesia's constitutional law, financial and environmental regulations, and judicial rulings. The study compares Indonesia's approach to environmental crimes using various technique with other countries policies and identifies areas for reform. The findings of this research highlight the urgency of uncovering contextual challenges that must be addressed, including the increasing use of digital platforms to anticipate green financial crimes, particularly in areas such as deforestation and environmental exploitation, through the proposal of green legislation. The present analysis underscores the necessity for Indonesia to adapt its legal and regulatory frameworks in order to tackle the environmental protection concerns brought about by the digital economy.